Scientists’ warning on sustainability: the ecologist point of view, with examples from marine ecosystems - Monica Montefalcone; Carla Morri; Carlo Nike Bianchi (Discover Sustainability)
Abstract In recent years, the urgency of achieving sustainability has become a central focus across various scientific disciplines due to the escalating impacts of human activities on the environment in the Anthropocene. In this contribution to the scientists’ warning series, we review key ecological insights essential for shaping sustainability strategies to mitigate environmental degradation, and we issue a warning on how sustainability should be pursued in response to these challenges. Drawing on the expertise of ecologists, who understand the complex interactions that underpin natural systems, we explore the balance between ecological, economic, and social dimensions of sustainability, providing examples of case studies on marine ecosystems. Fundamental ecological principles—such as biodiversity conservation, ecosystem services, resilience, and disturbance—are examined to highlight their role as the foundations of sustainable development. This review also underscores the importance of interdisciplinary collaboration in advancing sustainability practices that are both ecologically sound and socially viable. By identifying gaps in current knowledge and advocating for a paradigm shift toward prioritizing ecological integrity, we emphasize the urgent need for science-based policies to address today’s environmental issues. Ultimately, this work frames the human-nature relationship as central to sustainable development, calling for enhanced ecological awareness to combat global change, decelerate biodiversity loss, and promote environmental protection.